Should I be Concerned? Surgical Training in the Time of COVID19 - Zuberi, Maaz K (J Surg Educ, 2021)
As the US healthcare system restructured to deal with the COVID-19 pandemic, medical training was significantly disrupted. During the peak of the crisis, three surgical trainees in different stages of their residency shared their experiences and concerns on how this pandemic affected their training. The article is intended to generate discussion on the concerns of derailment and stagnation of surgical training and difficulties faced at all levels of surgical training to perform clinical duties and fulfill academic responsibilities during the early months of the COVID pandemic.